Biosafety Regulatory Reviews and Leeway to Operate: Case Studies From Sub-Sahara Africa - Komen, John; Tripathi, Leena; Mkoko, Boniface; Ofosu, Daniel Osei; Oloka, Herbert; Wangari, Doris (Frontiers in Plant Science, 2020)
While modern biotechnology and, specifically, genetic modification are subject of debate in many advanced economies, an increasing number of countries in Sub-Sahara Africa are making important strides towards authorizing general releases of genetically modified (GM) crop varieties for use by farmers and agribusinesses. Obviously, the documented economic and environmental benefits from planting GM crops – based on a track record of over 2 decades – are a major driver in the decision-making process. Another key factor is the increasing alignment of biosafety regulatory policies with progressive agricultural and rural development policies in Africa, resulting in greater emphasis on anticipated benefits rather than perceived risks in biosafety regulatory reviews. In a number of cases, this has led to expedited reviews of GM crop release applications, either for confined field trials or general environmental release, taking experiences from other countries into account. Such regulatory approaches hold promise as the pipeline of relevant, pro-poor GM applications is expanding as are the opportunities provided by novel plant breeding techniques. This review article analyses the shifting policy context in select African economies, resulting in increased adoption of new agricultural technology, and novel regulatory approaches used in biosafety decision-making. Case studies will be presented for Ghana, Kenya, Malawi, Nigeria and Uganda to distill lessons learned and to present general policy recommendations for emerging economies.